2012
DOI: 10.2147/ndt.s23317
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment of social phobia: systematic review and meta-analysis

Abstract: This article proposes a number of recommendations for the treatment of generalized social phobia, based on a systematic literature review and meta-analysis. An optimal treatment regimen would include a combination of medication and psychotherapy, along with an assertive clinical management program. For medications, selective serotonin reuptake inhibitors and dual serotonin-norepinephrine reuptake inhibitors are first-line choices based on their efficacy and tolerability profiles. The nonselective monoamine oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 105 publications
(148 reference statements)
0
26
0
1
Order By: Relevance
“…Early maltreatment is also a strong predictor of social phobia (Bruce, Heimberg, Blanco, Schneier, & Liebowitz, 2012;Lochner et al, 2010), one major symptom of which is social withdrawal (American Psychiatric Association, 2000). Psychotherapy for social phobia is reasonably successful in these conditions (Canton et al, 2012;Willutzki et al, 2012), while psychotherapy for violence produces more modest results later in life (Currie & Startup, 2012;Weiss et al, 2005). In line with these human findings, post-weaning social isolation in rats resulted in marked social deficits in social contexts, but these deficits were relatively rapidly abolished by group living.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Early maltreatment is also a strong predictor of social phobia (Bruce, Heimberg, Blanco, Schneier, & Liebowitz, 2012;Lochner et al, 2010), one major symptom of which is social withdrawal (American Psychiatric Association, 2000). Psychotherapy for social phobia is reasonably successful in these conditions (Canton et al, 2012;Willutzki et al, 2012), while psychotherapy for violence produces more modest results later in life (Currie & Startup, 2012;Weiss et al, 2005). In line with these human findings, post-weaning social isolation in rats resulted in marked social deficits in social contexts, but these deficits were relatively rapidly abolished by group living.…”
Section: Discussionmentioning
confidence: 61%
“…It was shown that these adverse early conditions contribute to excessive aggressive behavior in adolescence and adulthood (Krischer & Sevecke, 2008;Maxfield & Widom, 1996;McCord, 1983;Rivera & Widom, 1990;Widom, 1989). There are reports about possible pharmacological treatments for these symptoms, as well as about psychotherapy or cognitive behavior therapy, however, treatment efficacy is unsatisfactory (Canton, Scott, & Glue, 2012;Currie & Startup, 2012;Goedhard et al, 2006;McCloskey, Noblett, Deffenbacher, Gollan, & Coccaro, 2008;Turgay, 2004;B. Weiss et al, 2005;Willutzki, Teismann, & Schulte, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive-behavioral therapy (CBT) is the most effective psychosocial intervention for SAD (Gordon, Wong, & Heimberg, 2014), and CBT produces clinical improvements that are more enduring than those of pharmacotherapy (Canton, Scott, & Glue, 2012). Neuroimaging studies show that CBT modulates emotion processing brain networks (Clark & Beck, 2010; Porto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, additional research will be needed before this could occur; however, if this does become the case, a wealth of knowledge can be consolidated across disorders that can potentially be used to better understand, assess and treat clients. The latter is especially important, as the empirical literature on treatment options for SAD is far greater than for AvPD (Canton, Scott, & Glue, 2012).…”
Section: Limitations and Future Directionmentioning
confidence: 99%